The importance of using individual protection equipment (IPE) in times of covid-19 (Research, Society and Development, 2020)
The present study aimed to describe the importance of using personal protective equipment (IPE) in times of COVID-19. The present study is an exploratory research of the literature review type. For the development of this review, the following steps were taken: 1) definition of the theme and formulation of the guiding question, 2) establishment of inclusion and exclusion criteria, 3) definition of descriptors, 4) pre-selection of articles, 5) evaluation studies (interpretation of results) and 6) presentation of the review. The searches were carried out between february and April 2020, using the Scielo, Lilacs and Google scholar databases, with the time frame from 2016 to 2020. There was a careful selection with respect to the works used for the development of this review. The descriptors used, in an associated and isolated way, were: Risk, IPE, Prevention, Coronavirus and Health Professional, in English, Spanish and Portuguese and indexed in DeCS. 511 articles were found; however, after excluding duplicate and incomplete findings, it was restricted to 72 works, which were read individually by the researchers. 8 articles were used in the review. Therefore, in the face of a viral epidemic outbreak in the world, such as that experienced by the coronavirus, one can infer the importance of preventive methods when it comes to minimizing viral transmissions. Surgical masks and surgical respiratory protection have been playing an important role in controlling the spread of this new microorganism in the world and have been considered an excellent and accessible method for this.